NUMERICAL IMITATION AND ANALYSIS OF TRANSIENT ELECTROMAGNETIC PROCESSES AT THEIR EARLY STAGES - Cheryauka A.B.; Martakov S.V. (My University, 1999)
A one-dimensional TEM problem is solved with regard for wave processes in a nonmagnetic medium. Based on the disturbance and conjugate-equation methods, functions of the field sensitivity to model parameters (Frechet derivatives) have been obtained. Numerical modeling of transient processes at their early stages is carried out for various types of two-layer models.